2004
DOI: 10.1007/s00213-004-2096-z
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor antagonists improve the learning performance in memory-impaired rats

Abstract: These data suggest that dopamine D3 receptor antagonists possess cognition-enhancing activity which may be of benefit in the treatment of cognitive dysfunction associated with several psychiatric disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 37 publications
8
72
0
1
Order By: Relevance
“…Recent studies showed that D 3 blockade has an important role in enhancing memory, attention, and learning (Nakajima et al, 2013). Moreover, D 3 antagonists were shown to improve learning deficits in memoryimpaired rats (Laszy et al, 2005). The current findings are, therefore, most likely to be attributed to a specific effect on the ability of conditioned stimuli, previously paired with the Figure 2 The effect of SB-277011-A (0.01-1 mg/ml/side), or vehicle (0), locally infused into the basolateral amygdala (BLA; n ¼ 7; a), nucleus accumbens (NAcc; n ¼ 8; b), or lateral habenula (LHb; n ¼ 7; c) on the mean (±SEM) number of active (filled symbols) or inactive (open symbols) lever presses during cue-induced reinstatement of nicotine seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that D 3 blockade has an important role in enhancing memory, attention, and learning (Nakajima et al, 2013). Moreover, D 3 antagonists were shown to improve learning deficits in memoryimpaired rats (Laszy et al, 2005). The current findings are, therefore, most likely to be attributed to a specific effect on the ability of conditioned stimuli, previously paired with the Figure 2 The effect of SB-277011-A (0.01-1 mg/ml/side), or vehicle (0), locally infused into the basolateral amygdala (BLA; n ¼ 7; a), nucleus accumbens (NAcc; n ¼ 8; b), or lateral habenula (LHb; n ¼ 7; c) on the mean (±SEM) number of active (filled symbols) or inactive (open symbols) lever presses during cue-induced reinstatement of nicotine seeking.…”
Section: Discussionmentioning
confidence: 99%
“…The role of hippocampal dysfunction in the PD recollection and recall impairment is specifically supported by rodent and imaging studies of healthy human adults, which show that the hippocampus and the ventral tegmental area form a functional loop controlling the entry of novel and salient/goal-directed information into long-term memory (e.g., Bethus, Tse, & Morris, 2010;Bunzeck, et al, 2007;Chowdhury, Guitart-Masip, Bunzeck, Dolan, & Duzel, 2012;Gasbarri, Sulli, & Packard, 1997; for a review see Lisman & Grace, 2005). Dopamine D1 and D2 receptors are also implicated in the persistence/slow consolidation of hippocampal-dependent memories (Hammad & Wagner, 2006;Laszy, Laszlovszky, & Gyertyan, 2005;Lisman, et al, 2011;O'Carroll, Martin, Sandin, Frenguelli, & Morris, 2006;Takahashi, et al, 2008) …”
mentioning
confidence: 99%
“…Indeed, the use of D2/D3 family antagonists has been described for reducing the impairment of memory deficits induced by amnesic compounds in rodents [32]. This is also supported by the trend for OR facilitation in WT injected with 0.05 mg/kg haloperidol.…”
mentioning
confidence: 78%